The features of the use of color and light in the best works of the festival of video poetry “Videostikhiya” - Rudakova, Svetlana (Slavica, 2024)
This paper deals with video poetry as a phenomenon of contemporary art. A brief excursion into the history of video poetry is presented. The popularity of video poetry in the early 21st century is explained in this paper throughmany factors, one of which is the systematic, since 2002, holding of various festivals and contests of poetic video clips. The main attention is focused on the analysis of video clips presented at the international festival of video poetry ‘Videostichia’. The peculiarity of the use of such a technique as color in the best video clips is revealed. It is noted that video poetry revises the idea of color, making it more symbolic and memorable. Each clip transforms the ordinary perception of color, turning it into a symbol of art and life.